PENGARUH FAMILY CONTROL TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN PADA INDUSTRI BARANG KONSUMSI DI INDONESIA - Jessica Rissa Catherine; Aditya Septiani (Diponegoro Journal of Accounting, 2017)
This research aims to analyze the effect of family control on profitability and firm value for Consumer Good Industry in Indonesia. Family control as an independent variable is measured by dummy variable. Profitability and firm value as dependent variable are measured by ROA and Tobins q value. This research uses size, sales growth, and leverage as a control variable. The sample of this research is manufacturing companies on consumer goods industry sector listed in Indonesia Stock Exchange during the period 2012-2014. The sampling method in this research is purposive sampling. The analysis technique in this study using multiple regression analysis. Overall, the results show that family control has significant positive effects on the profitability. Family control is not affected on the firm value.